Building a comprehensive library of observed Lagrangian trajectories for testing modeled cloud evolution, aerosol–cloud interactions, and marine cloud brightening - E. Erfani; R. Wood; P. Blossey; S. J. Doherty; R. Eastman (Atmospheric Chemistry and Physics)
As the evolution of marine low clouds is sensitive to the current state of the atmosphere and varying meteorological forcing, it is crucial to ascertain how cloud responses differ across a spectrum of those conditions. In this study, we introduce an innovative approach to encompass a wide array of conditions prevalent in low marine cloud regions by creating a comprehensive library of observed environmental conditions. Using reanalysis and satellite data, over 2200 Lagrangian trajectories are generated within the stratocumulus deck region of the Northeast Pacific during summer 2018–2021. By using eight important cloud-controlling factors (CCFs), we employ principal component analysis (PCA) to reduce the dimensionality of data. This technique demonstrates that two principal components capture 43 % of the variability among CCFs. Notably, PCA facilitates the selection of a reduced number of trajectories (e.g., 54) that represent a diverse array of the observed CCF, aerosol, and cloud variability and co-variability. These trajectories can then be used for process model studies, e.g., with large-eddy simulations (LES), to evaluate the efficacy of marine cloud brightening. Two distinct cases are selected to initiate 2 d long, high-resolution, large-domain LES experiments. The results highlight the ability of our LES to simulate observed conditions. Although perturbed aerosols delay cloud breakup and enhance the cloud radiative effect, the strength of such effects is sensitive to “precipitation-aerosol feedback”. The first case is precipitating and shows the potential for “precipitation-driven” cloud breakup due to positive precipitation-aerosol feedback. The second case is non-precipitating with classic cloud breakup of the “deepening-warming” type, highlighting the impact of entrainment.